PENGARUH MINAT BELAJAR DAN CARA BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA KELAS XI AKUNTANSINDI SMKN 1 PULAU PUNJUANG - Elfiyanti, Riska - (Pendidikan Ekonomi, 2014)
This research aim  to to know how far influence of enthusiasm learn and way of learning student to result learn class student of XI Accountancy in SMKN I Island of Punjung. his research pertained to descriptive research type with quantitative approach. Population in this  research  is entire/all class siswa-siswi of XI Accountancy in SMKN l Island ofPunjung School Year 2013 I 204 amounting to 60 people. technique of Sampel done/conducted totally sampling with amount of sampel counted 60 student people. Data the analysed is collected primary  data pass/through spreading of enquette with scale of Iikert data and of sekunder obtained from data result  of learning class of XI Accountancy in SMKN 1 Island ofPunjung even semester 2013 I 2014. While data use inductive and descriptive analysis consist of test of likelihood, test Ramsey,  test normalitas,  test multikolinearitas, test heteroskedastisitas,  test autokorelasi, doubled linear regression test, coefficient test of determinasi ( R Sguare) and hypothesis test. Result of research indicate that ( I) there are influence of enthusiasm signifikan learn to result learn class student of XI Accountancy in SMKN I Island of punjung where value of thitung ( 6,079) > t abel ( I ,670) and sig ( 0,000) ? ( 0,05), its meaning of H0 refused and Is ha accepted. ( 2) there are influence of signifikan of is way of learning to result learn class of XI Accountancy in SMKN I Island of Punjung where value of tru w g ( 6,079) > tube1 ( I ,670) and sig ( 0,000)? ( 0,05), its meaning ofHo refused and Is ha accepted. ( 3) enthusiasm  variable  learn and way of learning together have an effect on positive and signifikan to result learn class of XI Accountancy  in SMKN I Island ofPunjung where value ofFbitung ( 68,778) >from Ftabct ( 3,15) and sig ( 0,000) <from alpha ( its 0,05) meaning offio refused and Is ba accepted.